Priority strategy for increasing produced revenue of halal frozen food during the Covid-19 pandemic in Bogor, Indonesia - Gandhi, Prima; Anggraini, Sanitianing; Salsabilah, Muhammad Fazra; Yulianti, Alma Shopia (IPB University, 2024)
Frozen food was first offered in United States supermarkets by Clarence Birdeye in 1930 and the trend of increasing consumption was experienced during the Covid-19 pandemic. Increasing demand for frozen food requires consumers to choose the best option. Consumers prefer to competitively produce make production efficient, introduce products, and gain wider market share. The biggest consumer preference in Indonesia is for halal-frozen food. In this context, PT XYZ is a halal frozen food manufacturer attempting to increase market share to ensure high revenue. This company plans to pasteurise egg raw materials and optimise digital marketing of halal frozen food using the TikTok application to increase revenue. Therefore, this study aimed to analyse the financial aspects of the pasteurise process for egg raw materials and optimising digital halal frozen food marketing using the TikTok application, as well as determine the best efforts to increase revenue. The analytical method used was graphical descriptive and quantitative tabulation, including profit, loss, and R/C ratio analysis. The result showed that efforts to optimise halal frozen food digital marketing using the TikTok application were prioritised with a net profit of the IDR. 1,175,802,072 and an R/C ratio of 2.52.